MULTI-CRITERIA EVALUATION OF TEMPORARY WASTE COLLECTION FACILITIES BASED ON THE LEVEL OF COMMUNITY INTEREST USING ANALYTICAL HIERARCHY PROCESS - Purwani, A.; Fauzia, S.; Linarti, U.; Md Fauadi, M.H.F.; Haryoko, A. (Journal of Advanced Manufacturing Technology (JAMT), 2024)
Waste management poses a complex challenge for governmental bodies. One of the challenges involves balancing the interests among various stakeholders, including city residents and local authorities, regarding the establishment of temporary waste collection facilities. A comprehensive examination of waste management issues should encompass operational, technical, financial, institutional, regulatory, and community aspects. This study aimed to evaluate and identify the criteria for the provision of temporary waste collection facilities and services from a community perspective. The criteria were determined by distributing open questionnaires to the community residing near the facilities. Additionally, reference studies were conducted to reinforce the community’s perspectives. Analytical hierarchy process (AHP) was employed to determine the importance level of each criterion. The research was conducted in 75 facilities across three sectors (eight sub-districts) in Yogyakarta. Purposive sampling was utilised based on the population distribution in each sub-district, with the sample sizes determined using the Slovin method. The findings of the study showed that almost all sub-districts in these three sectors had two identical highest criteria: health (24%) and distance (22%). These criteria underscore the necessity for the government to prioritise health and distance considerations over the operational aspect of waste collection.